2021
DOI: 10.3390/molecules26071998
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Oxide Nanoparticles and Zinc Sulfate Impact Physiological Parameters and Boosts Lipid Peroxidation in Soil Grown Coriander Plants (Coriandrum sativum)

Abstract: The objective of this study was to determine the oxidative stress and the physiological and antioxidant responses of coriander plants (Coriandrum sativum) grown for 58 days in soil with zinc oxide nanoparticles (ZnO NPs) and zinc sulfate (ZnSO4) at concentrations of 0, 100, 200, 300, and 400 mg of Zn/kg of soil. The results revealed that all Zn compounds increased the total chlorophyll content (CHLt) by at least 45%, compared to the control group; however, with 400 mg/kg of ZnSO4, chlorophyll accumulation decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…When NPs are applied to the soil or in the irrigation water, they penetrate through the epidermis of the root and the bark, later they pass to the endodermis, and finally they enter the conductive tissue of the xylem to be translocated by a long distance to the branches and the foliage of plants [66]. In addition, it presents a slow and gradual availability of the active ingredient, which results in greater efficiency [68].…”
Section: Translocation Of Zno and Tio 2 Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…When NPs are applied to the soil or in the irrigation water, they penetrate through the epidermis of the root and the bark, later they pass to the endodermis, and finally they enter the conductive tissue of the xylem to be translocated by a long distance to the branches and the foliage of plants [66]. In addition, it presents a slow and gradual availability of the active ingredient, which results in greater efficiency [68].…”
Section: Translocation Of Zno and Tio 2 Nanoparticlesmentioning
confidence: 99%
“…Nevertheless, it is known that nanomaterials are considered a stress factor in plants since there is the possibility that they can remodel and modify the structure and constitution of membranes and cell walls in plants [63,94]. However, the phytotoxicity of NPs as a plant fertilizer and/or pesticide is determined by the applied concentration, the dissolution of its ionic forms, and the absorption and transport of the active element and its accumulation in plant tissues [68]. Once the NPs have penetrated the plant tissue, they present a slow and gradual availability of the active ingredient at the cellular level, which results in a greater accumulation of the ++ ion and, therefore, the generation of oxidative stress [95,96].…”
Section: Phytotoxicity In the Plant By Nanoparticlesmentioning
confidence: 99%
“…The second phase is believed to occur in response to the internment and metabolism of NMs, possibly by the release of Zn 2+ ions in plant cells (Juárez-Maldonado et al, 2019). The production of reactive or oxidizing species, such as H2O2, activates plant defense systems, increasing the activity levels of enzymes such as CAT, APX, and GPX, as well as the concentration of nonenzymatic antioxidants such as phenols and flavonoids (Abdel-Aziz et al, 2019;Ruiz-Torres et al, 2021).…”
Section: Greenhouse Stage (45 Das)mentioning
confidence: 99%
“…On the other hand, seed priming with NMs can increase the activity of enzymatic antioxidants and the concentration of nonenzymatic antioxidants due to two mechanisms: one is NM corona contact with the cell wall, favoring the generation of reactive chemical species, and the other is believed to occur in response to the internment and metabolism of NMs, possibly by the release of ions in plant cells (Juárez-Maldonado et al, 2019). The production of reactive or oxidizing species, such as H2O2, activates plant defense systems, increasing the activity levels of enzymes such as CAT, APX, and GPX, as well as the concentration of nonenzymatic antioxidants such as phenols and flavonoids (Abdel-Aziz et al, 2019;Ruiz-Torres et al, 2021). Some studies found that the application of NZnO favored increased activity of SOD, CAT, POD, and APX in Lupinus ternis plants (Abdel-Latef et al, 2017) and increased activity of CAT, APX, and POD in Coriandrum sativum (Ruiz-Torres et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation